INFLUENCE OF SCHOOL PRINCIPAL PERFORMANCE IN TERMS OF SCHOOL CLIMATE FACTORS, MANAGERIAL COMPETENCE AND SUPERVISION COMPETENCE, CASE STUDY IN MEDAN CITY VOCATIONAL SCHOOL - MIAN SIAHAAN (JURNAL ILMIAH KOHESI, 2020)
This study is intended to discuss and describe three hypothesis; (1) partially and managerial competence and principal supervision competence directly influence the school climate, (2) partially and together with managerial competence, supervisory competence and school climate directly influence the performance of school principals and (3) partially managerial competence, supervision competence indirectly affects the performance of SMK headmasters in the city ​​of Medan, North Sumatra Province through the school climate. This research is based on the quality problem of Vocational High Schools (SMK) in Medan, North Sumatra Province. This can be seen from the rank of vocational high schools in Medan at the level of the Province of North Sumatra in competency test activities, national student skills competitions (LKS) and the number of unemployed graduates of vocational schools from Medan . Through this data it is assumed that the management of the learning process in general vocational yet optimal due to the ability of managerial competence, competence supervision principals who subsequently will affect the performance of the principal in managing schools. Good and professional school management is one indicator of school successfulness. This research was conducted by using quantitative methods with descriptive and associative research types. The population numbered 181 people consisting of one 68 people from private vocational and 13 people from government SMK and the number is an entire head of SMK existing in the city of Medan. The number of samples taken was 54 people with proportional random sample. The research data was collected using a questionnaire. Hypothesis testing is done by using descriptive and analytical path. The study findings showed that managerial competence partially enormous influence 80.25% to performance headmaster. Competency partial supervision of the school head master can improve the performance of the principal by 75,5%. Furthermore, improving the competence of the managerial and competence supervision, together can improve the performance of principals and can account for as much as 86%. The school climate variable is an exogenous variable which has the greatest path coefficient on the principal's performance compared to other exogenous variables which is equal to 0.420. Based on the research findings, it can be concluded that (1) partially and together managerial competence and principal supervision competence directly influence the school climate of the SMK city ​​of Medan, (2) managerial competence, supervision competence, and the school climate partially and together directly influences the performance of the head mater SMK city of Medan, and (3) managerial competence, supervision competency partially has an indirect effect on the performance of the head master vocational school in Medan through the school climate.